Prove the following


$\int \frac{2 x+3}{x^{2}+3 x} d x=\log \left|x^{2}+3 x\right|+C$


L.H.S. $=\int \frac{2 x+3}{x^{2}+3 x} d x$

Putting, $\quad x^{2}+3 x=t$

So, $\quad(2 x+3) d x=d t$

$\Rightarrow \quad \int \frac{d t}{t}=\log |t| \Rightarrow \log \left|x^{2}+3 x\right|+\mathrm{C}=$ R.H.S.

L.H.S. $=$ R.H.S

- Hence proved.

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now